Plan de promoción turística para dinamizar el turismo interno en la provincia de Manabí - Loor Cedeño, Katherine Lisbeth (2023)
The main objective of this research is to develop a tourism promotion plan to boost domestic tourism in Manabí providence, it was developed in three phases, the analytical, descriptive, synthetic and quantitative methods were applied; starting with a tourist diagnosis where the study area was analyzed, the physical and demographic characteristics of the province were described; we proceeded to analyze the current situation of the promotion of tourism, in this way it was possible to identify the reality of the promotion of resources and attractions in the province; in the second phase, a market study was carried out where supply, demand and competition were analyzed, tools such as surveys and competition matrix were applied, this helped to identify the current state of the promotion of the cantons of the province. In the third phase, the strategies of the promotion plan were determined, a tourist brand of Manabí was created, as well as a slogan, advertising brochure, social networks and a content schedule where the dates of the tourist activities of each canton are highlighted. In the same way, the control and monitoring of said plan was proposed, all this will allow the integration and participation of local public, private and business actors, facilitating the process of commercialization of the resources, products and services of the province of Manabí, and of this way to promote by means of the promotion and tourist publicity attracting greater affluence of the tourists.